Determinación de Aldolasa A como marcador de sobreentrenamiento físico en el club deportivo Río Amarillo del cantón Portovelo, provincia de El Oro - Jaramillo Salto, Roxana P. (2008)
There are diverse illnesses that can be caused by the alteration of the enzyme Aldolasa “A”, the elevation of this enzyme not only affects people that are in constant physical exercise as the youths but rather it also affects people of quite mature age.